Osjetljivost dijagnostičkih parametara vibracijskog signala cilindra motora - Ivan Mavrin (Promet (Zagreb), 2012)
This paper deals with respective diagnosing parameters for establishing the cylinder wear condition. The amplitude of cylinder acceleration at dominant frequencies and the moment of the piston stroke in to the cylinder expressed by the angle of the crankshalt have been analysed as the diagnosing parameters. The accuracy of the obtained diagnosing parameters has been tested. This property is of major importance, because if missing, the selected diagnosing parameter cannot be used in a reliable manner for establishing the value of the structural parameter. The accuracy of delined diagnosing parameters has been tested in an experiment for different values of the engine cylinder wear condition.